The Nature of the Institution of Military Slavery and Government is Anushteginid (Zien Journal of Social Sciences and Humanities, 2022)
Until now, on the issue of the level of slavery in the Anushteginid state, especially on the nature of the social stratum of military slavery - Ghulams or Mamluks, the social status of these strata, their way of life has not been scientifically analyzed and is an unresolved problem. At the moment, in order to reveal the essence of slaveholding relations in the Anushteginid state, it is necessary to pay attention to two main issues. First of all, as an Islamic state, it is appropriate to deeply analyze the question of how slavery is classified as slavery on the basis of Islamic moral rules. Secondly, it is necessary to identify the types, sources and characteristics of slaves that distinguish them from slavery in other countries. Therefore, this article attempts to analyze the problem based on new views and approaches.